Fen eğitiminde öğrenme amaçlı yazmaya yönelik yapılan ulusal ve uluslararası lisansüstü tezlere ait bir sentez çalışması - BENZER, ELİF (My University, 2022)
The aim of this study is to examine and analyse the postgraduate thesis studies published in the national and international fields for writing for learning purposes in science education in the context of the determined criteria. For this purpose, national and international postgraduate theses prepared for writing in science education between 2010-2020 were reached and 37 national and 36 international thesis studies included in the study were examined. This study, which examines the theses prepared for writing in the field of science education, was carried out as a synthesis study and in this direction, 73 postgraduate theses were examined with a comprehensive and critical approach. As a result of the examination; In most of the national and international postgraduate theses, writing themes related to science achievement, science attitude, conceptual learning and scientific skills are preferred, theses are mostly carried out with experimental methods from quantitative research methods, mostly secondary school samples are studied, and academic achievement test is generally used as a data collection tool and t-test analyses were used in the analysis process. In addition, within the framework of the thesis studies analysed, it was revealed that writing activities had a positive effect on academic achievement, attitude, writing skills, writing proficiency, and creative writing levels. International theses; It has been determined that it differs from national theses with the themes of science news, professional development, technology-integrated writing, and information transformation. Based on the results of the study, it is suggested that the postgraduate theses, especially in the national field, conducted for writing for learning purposes in science education, are enriched from different aspects (scientific method, approach, subject, etc.) to fill the gap in this subject with studies.

Bu çalışmanın amacı, fen eğitiminde öğrenme amaçlı yazmaya yönelik yapılan ulusal ve uluslararası alanda yayımlanan lisansüstü tez çalışmalarının belirlenen ölçütler bağlamında incelenerek analiz edilmesidir. Bu amaç doğrultusunda 2010-2020 yılları arasında fen eğitiminde yazmaya yönelik hazırlanan ulusal ve uluslararası lisansüstü tezlere ulaşılmış ve çalışma kapsamına giren 37 ulusal ve 36 uluslararası tez çalışması incelenmiştir. Fen eğitimi alanında yazmaya yönelik hazırlanan tezlerin irdelendiği bu çalışma, bir sentez çalışması olarak yürütülmüş ve bu doğrultuda 73 lisansüstü tez kapsamlı ve eleştirel bir yaklaşımla incelenmiştir. İnceleme sonucunda; ulusal ve uluslararası lisansüstü tezlerin çoğunda fen başarısı, fen tutumu, kavramsal öğrenme ve bilimsel becerilere ilişkin yazma temalarının tercih edildiği, tezlerin çoğunlukla nicel araştırma metotlarından deneysel yöntemlerle yürütüldüğü, en fazla ortaokul düzeyindeki örneklemler üzerinde çalışıldığı, genellikle veri toplama aracı olarak akademik başarı testinden yararlanıldığı ve analiz sürecinde t-testi analizlerine başvurulduğu belirlenmiştir. Ayrıca analiz edilen tez çalışmaları çerçevesinde; fen bilimleri akademik başarısı, tutumu, yazma becerileri, yazma yeterlilikleri, yaratıcı yazma düzeyleri üzerinde yazma faaliyetlerinin olumlu anlamda etkisi olduğu ortaya konulmuştur. Uluslararası tezlerin; bilim haberleri, mesleki gelişim, teknoloji entegrasyonlu yazma, bilgiyi dönüştürme temalarıyla ulusal tezlerden ayrıştığı tespit edilmiştir. Çalışma sonuçlarından hareketle fen eğitiminde öğrenme amaçlı yazmaya yönelik yürütülen özellikle ulusal alanda bulunan lisansüstü tezlerin farklı açılardan (Bilimsel yöntem, yaklaşım, konu vb.) zenginleştirilerek bu konudaki açığın yapılan çalışmalarla doldurulması önerilmektedir.
A synthesis study of national and international graduate theses on writing for learning in science education
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Science education; Graduate theses; Writing for learning; Synthesis study; TO-LEARN; SECONDARY SCIENCE; MIDDLE SCHOOL; METASYNTHESIS